Association of Body Composition Changes with the Development of Diabetes Mellitus: A Nation-Wide Population Study - Hyung Jun Kim; Hyung-Woo Lee; Min-Kyoung Kang; Gwang Hyun Leem; Min-Ho Kim; Tae-Jin Song (Diabetes & Metabolism Journal)
Background We investigated the association between body composition changes and new-onset diabetes mellitus (DM) development according to the body mass index (BMI) in a longitudinal setting in the general Korean population. Methods From 2010 to 2011 (1st) and 2012 to 2013 (2nd), we included 1,607,508 stratified random sample participants without DM from the National Health Insurance Service-Health Screening dataset of Korean. The predicted appendicular skeletal muscle mass index (pASMMI), body fat mass index (pBFMI), and lean body mass index (pLBMI) were calculated using pre-validated anthropometric prediction equations. A prediction equation was constructed by combining age, weight, height, waist circumference, serum creatinine levels, alcohol consumption status, physical activity, and smoking history as variables affecting body composition. Results Decreased pASMMI (men: hazard ratio [HR], 0.866; 95% confidence interval [CI], 0.830 to 0.903; P<0.001; women: HR, 0.748; 95% CI, 0.635 to 0.881; P<0.001), decreased pLBMI (men: HR, 0.931; 95% CI, 0.912 to 0.952; P<0.001; women: HR, 0.906; 95% CI, 0.856 to 0.959; P=0.007), and increased pBFMI (men: HR, 1.073; 95% CI, 1.050 to 1.096; P<0.001; women: HR, 1.114; 95% CI, 1.047 to 1.186; P=0.007) correlated with the development of new-onset DM. Notably, only in the overweight and obese BMI categories, decreases in pASMMI and pLBMI and increases in pBFMI associated with new-onset DM, regardless of gender. Conclusion Decreased pASMMI and pLBMI, and increased pBFMI with excess fat accumulation may enhance the risk of newonset DM. Therefore, appropriate changes in body composition can help prevent new-onset DM.